New Insights into Reelin-Mediated Signaling Pathways - Lee, Gum Hwa; D’Arcangelo, Gabriella (Frontiers in Cellular Neuroscience, 2016)
Reelin, a multifunctional extracellular protein that is important for mammalian brain development and function, is secreted by different cell types in the prenatal or postnatal brain. The spatiotemporal regulation of Reelin expression and distribution during development relates to its multifaceted function in the brain. Prenatally Reelin controls neuronal radial migration and proper positioning in cortical layers, whereas postnatally Reelin promotes neuronal maturation, synaptic formation and plasticity. The molecular mechanisms underlying the distinct biological functions of Reelin during and after brain development involve unique and overlapping signaling pathways that are activated following Reelin binding to its cell surface receptors. Distinct Reelin ligand isoforms, such as the full-length protein or fragments generated by proteolytic cleavage differentially affect the activity of downstream signaling pathways. In this review, we discuss recent advances in our understanding of the signaling transduction pathways activated by Reelin that regulate different aspects of brain development and function. A core signaling machinery, including ApoER2/VLDLR receptors, Src/Fyn kinases, and the adaptor protein Dab1, participates in all known aspects of Reelin biology. However, distinct downstream mechanisms, such as the Crk/Rap1 pathway and cell adhesion molecules, play crucial roles in the control of neuronal migration, whereas the PI3K/Akt/mTOR pathway appears to be more important for dendrite and spine development. Finally, the NMDAR and an unidentified receptor contribute to the activation of the MEK/Erk1/2 pathway leading to the upregulation of genes involved in synaptic plasticity and learning. This knowledge may provide new insight into neurodevelopmental or neurodegenerative disorders that are associated with Reelin dysfunction.